1983
DOI: 10.1161/01.res.53.6.815
|View full text |Cite
|
Sign up to set email alerts
|

Electrical and mechanical restitution of the human heart at different rates of stimulation.

Abstract: Action potential duration and contractility are reduced following premature excitations, and gradually increase as the stimulus interval is lengthened. To examine these phenomena of electrical and mechanical restitution in the human heart, we simultaneously measured action potential duration and the maximum rate of left ventricular pressure in five patients undergoing electrophysiological study. Test beats were introduced at varying intervals after the last of a series of steady state intervals. By plotting ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
61
0
1

Year Published

1987
1987
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 106 publications
(69 citation statements)
references
References 34 publications
7
61
0
1
Order By: Relevance
“…We never saw biphasic APD restitution curves (11,21,24,50) in which the ventricular myocardial restitution curve has a local maximum at short DI. The action potentials at this peak have been referred to as supernormal premature action potentials (3) and are believed to reflect potentiation of the calcium current.…”
Section: Resultsmentioning
confidence: 77%
“…We never saw biphasic APD restitution curves (11,21,24,50) in which the ventricular myocardial restitution curve has a local maximum at short DI. The action potentials at this peak have been referred to as supernormal premature action potentials (3) and are believed to reflect potentiation of the calcium current.…”
Section: Resultsmentioning
confidence: 77%
“…Initial conditions and the resulting dynamics may also change over intermediate time scales, such as following periods of sustained pacing, during which memory may accumulate (30, 71,75,79,106,151,206,218). Typically, accumulation of memory flattens APD restitution, an effect that results from augmented rate-dependent activation of the delayed rectifier (75,101,102) and by increased inward rectifier (221).…”
Section: Role Of Cardiac Dynamics In the Generation Of Ventricular Armentioning
confidence: 99%
“…Beat-to-beat changes in electrophysiological properties occur over seconds during irregular or rapid cardiac activation and appear to be important determinants of the propensity to develop and sustain arrhythmias, particularly as they relate to the development of dynamical heterogeneity of refractoriness (23, 83,84,186). On a longer time scale of minutes to hours, key electrical properties such as action potential duration (APD) are importantly influenced by an accumulation and dissipation of shortterm cardiac memory, as occurs during prolonged pacing (30,71,79,106). At a still longer time scale of days to months, the heart can remodel, both structurally and functionally, in response to various stressors (3,146,196).…”
Section: Introductionmentioning
confidence: 99%
“…4A). Experimental studies of restitution in human myocardium have also shown biphasic restitution curves (15,28). This phenomenon is still poorly understood and, so far, no ionic models have been developed to reproduce these nonmonotonic curves.…”
Section: Restitution Propertiesmentioning
confidence: 99%